PENGGUNAAN SIMULASI PHET TERHADAP EFEKTIFITAS BELAJAR IPA - Syarifah Rahmiza Muzana; Silvi Puspa Widya Lubis; Wirda Wirda (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
PhET Simulation is a free software created by the University of Colorado in the United States. The learning process by using this PhET simulation students can study certain material directly independently by using a computer which is equipped with the PhET program. The method in writing this article uses qualitative research methods. The data that has been collected is then analyzed so that it can be concluded that; 1) PhET simulation is an effective learning medium to increase student learning effectiveness; 2) The PhET simulation can help students learn without having to use a real laboratory; 3) by utilizing phet simulation media it is also able to improve students' ICT literacy skills; 4) How to use the PhET simulation is very easy and understandable according to the science lesson material; 5) The PhET simulation can be used for independent study at home without having to be supervised by the teacher at school.